Family and Work: Challenges to Labor, Management and Government - Cook, Alice (Relations industrielles / Industrial Relations, 1987)
Radical changes have taken place in family and in work over the last century. These two institutions are the source of conflicting demands. Accomodation calls both for equality in the home and for the restructuring of work.